APPLICATION OF MINERAL PLUS FERTILIZER TO INCREASE TOMATO PRODUCTION AND QUALITY IN BATURITI DISTRICT, TABANAN REGENCY, BALI PROVINCE, INDONESIA - Lanya, Indayati (International Journal of Biosciences and Biotechnology; Vol 9 No 2 (2022): INTERNATIONAL JOURNAL OF BIOSCIENCES AND BIOTECHNOLOGY, 2022)
Environmentally friendly agriculture and food health are needed to support tourism in Bali. Meanwhile, it is alleged that agricultural products do not meet the requirements, especially the quality that does not meet consumer requirements. This research refers to the Udayana University Research Master Plan, a leading field of food security. Food Security Research Roadmap, with the aim of producing appropriate technology. The research products can be implemented in activities to increase production, quality of horticultural crops and food health to support tourism. The research method was through testing the productivity and quality of tomato plants through the addition of organic fertilizers, mineral fertilizers, chemical fertilizers, and their combination. The highest production was obtained from the treatment of P6 = mineral plus fertilizer (5 tons of hill lime + 5 tons of organic fertilizer  products organic fertilizer product simantri + 100 kg urea + 100 kg phonska) per ha, can increase production (34.46%).   Treatment of mineral fertilization (P2) =mineral fertilizer 5 tons of hill limestone,  contains the highest vitamin C (286.14 mg/kg), P2 is also able to neutralize heavy metals Cu and Mo, increase calcium content, increase shelf life, thicken tomato skin walls which Calcium sticks to tomato skin.